Recycling Agricultural Waste from Palm Shells during Electric Arc Furnace Steelmaking - Nur Farhana, M. Yunos; Magdalena, Zaharia; M. Asri, Idris; Nath, Dilip; Khanna, Rita; Sahajwalla, Veena (American Chemical Society, 2013)
Link to publisher’s homepage at http://pubs.acs.org/page/enfuem/about.html